Design And Fabrication Of Integrated Parabolic Reflector Nano-Antenna Coupled Infrared Detector - Mubarak Ramadan, Mohamed Habashy (2018)
This work focuses upon the design and fabrication process of a novel parabolic reflector integrated nano-antenna coupled Infrared (IR) detector which is presented here for the first time. As this device stems from antenna coupled IR detectors, it will still also offer the advantages of the fast response, uncooled operation, frequency selectivity, polarization sensitivity and CMOS compatibility. However, the challenging fabrication techniques limited researchers’ work in many aspects. Most of the research in the literature was thus confined to 2D antenna design only, while developing the fabrication process through 3D micro-machining can add more varieties of 3D high gain antenna structure such as the parabolic reflector antenna proposed through this work. Such a structure is theoretically expected to add a space diversity gain and reduce the substrate mode losses. Therefore, the new structure has a high promising potential for efficiently increasing the specific detectivity of these devices paving the way towards commercialization. The fabrication process is presented and optimized through this work facilitated mainly by automated EBL and XeF2 etching. The structure is designed of seven layers encountering a 4.2 µm half wave dipole feeding antenna for operation in the long wave infrared band (LWIR) at wavelength 10.6 µm coupled with a 450 nm × 750 nm niobium batch as a sub-wavelength localized bolometric sensor. The SU8-10 photoresist is used permanently for low cost insulating and flat cavity filling purposes showing a height variation of less than 400 nm over the whole cavity aperture through the morphology analysis. The integrated parabolic cavity has 75 µm and 13 µm on average for its aperture diameter and cavity depth respectively. The presented XeF2 etching analysis reveals that, according to the proposed structure design, the proper etching recipe is described by 5 cycles, with 30 s each, at an etching gas pressure of 3 Torr. This recipe is sufficient to etch approximately a total volume of 0.3425 mm3, resulting in the required cavity profile, through a 2.2 µm SU8 mask that provides mainly circular windows pattern of 38 µm in diameter and few markers representing a total patterned area of 3.7122 mm2. The different geometrical analyses that are encountered for characterizing the fabrication process have been presented and the SEM of final structure has showed a good agreement with the proposed design. The I-V measurements have showed, however, non-linear characteristics with an extremely high impendence of 222 kΩ that hinder introducing the fabricated devices for the optical measurements. This problem is referred to the non-clean liftoff as it results in discontinuity of all the fabricated devices’ layers. A detailed discussion with the aid of the statistical analysis had been finally presented. The fabrication process of this device is thus presented successfully including micro-machining and patterning techniques, but more efforts can be encountered in the future work to overcome the highlighted issues and introduce the proposed device to the field.